Comparative Analysis on the Efficiencies of Unmodified Clay and Microorganism-Modified Clay as Adsorbent for the Adsorption of Lead (II) Ions from Wastewater - OPUTE, Cletus C.; OKWONNA, Obumneme O. (FUDMA Journal of Engineering and Technology, 2026)
Comparative study of the efficiencies of clay adsorbents (unmodified and microorganism- modified clay) in the adsorption of  lead (II) ion from wastewater was studied  as a function of some operating conditions, such as initial concentration, pH, agitation time, and temperature. The maximum adsorptive capacity of unmodified clay and the clay modified with microorganisms were found to be 30.40 mg/g and 42.22 mg/g respectively. Thermodynamics parameters evaluation gave a negative value of ΔHo of -4967.4 J/mol and -4655 J/mol for UMC and MMC respectively, indicating the exothermic nature of the process. Also, the negative value of ΔSo of -20.87 J/mol and -14.77 J/mol for UMC and MMC respectively reflect the increasingly orderliness of the adsorption system as the metal ions were been attached to the adsorbent surface. The adsorption of lead (II) ions onto unmodified and microorganism modified clay was favoured by Freundlich isotherm model. The heterogeneity factor (n) for UMC and MMC were less than one (n < 1) which indicates the process of adsorption was chemical and non-linear. Furthermore, Freundlich constant (KF) related to adsorption capacity for UMC and MMC was 2.01 mg/g and 2.16 mg/g respectively, confirming that the adsorption capacity of microorganism-modified clay is greater than that of the unmodified clay.
Keywords: Clay, lead (II) ion, adsorption, microorganism, isotherms.